The Labor Illusion: How Operational Transparency Increases Perceived Value - Buell, Ryan W.; Norton, Michael I. (Management Science, 2011)
Aubiquitous feature of even the fastest self-service technology transactions is the wait. Conventional wisdom and operations theory suggest that the longer people wait, the less satisfied they become; we demonstrate that because of what we term the labor illusion, when websites engage in operational transparency by signaling that they are exerting effort, people can actually prefer websites with longer waits to those that return instantaneous results—even when those results are identical. In five experiments that simulate service experiences in the domains of online travel and online dating, we demonstrate the impact of the labor illusion on service value perceptions, demonstrate that perceptions of service provider effort induce feelings of reciprocity that together mediate the link between operational transparency and increased valuation, and explore boundary conditions and alternative explanations. This paper was accepted by Pradeep Chintagunta and Preyas Desai, special issue editors. This paper was accepted by Pradeep Chintagunta and Preyas Desai, special issue editors.